A new species of the genus Mallomonas (Synurales, Chrysophyceae), Mallomonas fimbriata, sp. nov. - Gusev, Evgeniy Sergeevich (Phytotaxa, 2015)
Mallomonas fimbriata, sp. nov. is described from bog pool, located in Cam Ranh Peninsula, Khanh Hoa Province, Central Vietnam. The description is based on silica-scale morphology studied by means of transmission and scanning electron microscopy. New species has 3 types of scales: oval body scales, caudal ones with robust, long, forward pointing spines and elongated, widened to distal part apical scales. Scales are thick, 3-layered, with inner reticulation. Mallomonas fimbriata and the similar M. fenestrata form a special group with unique features of scales structure close to the sections Retrorsae and Quadratae.